2019
DOI: 10.1002/ijc.32785
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the expression of the immune checkpoint molecules PD‐1, CTLA4, TIM‐3 and LAG‐3 across different cancers in relation to treatment response, tumor‐infiltrating immune cells and survival

Abstract: Immune checkpoint molecules have been identified as crucial regulators of the immune response, which motivated the emergence of immune checkpoint‐targeting therapeutic strategies. However, the prognostic significance of the immune checkpoint molecules PD‐1, CTLA4, TIM‐3 and LAG‐3 remains controversial. The aim of our study was to conduct a systematic assessment of the expression of these immune checkpoint molecules across different cancers in relation to treatment response, tumor‐infiltrating immune cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
93
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(115 citation statements)
references
References 38 publications
(71 reference statements)
6
93
4
Order By: Relevance
“…Back to the question posed at the beginning of this section, LAG3 expression was found to be associated with poor clinicopathological factors and eliciting immune suppressive function, supporting the hypothesis that the expression of LAG3 in breast cancer patients should lead to poor survival. However, inconsistent with the present results, the ndings of several previous studies indicated a favorable association between high expression of LAG3 and cancer-speci c survival, especially in ER-, HER2 + and basal-like subtypes (47,66,67). Interestingly, another published study found that serum LAG3 had a close correlation with prolonged survival in ER + patients (42).…”
Section: Discussioncontrasting
confidence: 99%
“…Back to the question posed at the beginning of this section, LAG3 expression was found to be associated with poor clinicopathological factors and eliciting immune suppressive function, supporting the hypothesis that the expression of LAG3 in breast cancer patients should lead to poor survival. However, inconsistent with the present results, the ndings of several previous studies indicated a favorable association between high expression of LAG3 and cancer-speci c survival, especially in ER-, HER2 + and basal-like subtypes (47,66,67). Interestingly, another published study found that serum LAG3 had a close correlation with prolonged survival in ER + patients (42).…”
Section: Discussioncontrasting
confidence: 99%
“…Immune checkpoints commonly play significant roles in triggering the cancer immunity escape by mediating the interaction between tumor cells and TIICs, so their expressions were commonly positively correlated with TIICs abundance [32,33]. In our research, we found that the high infiltration of TIICs predicted worse outcomes in total LGG patients.…”
Section: Discussionsupporting
confidence: 49%
“…Besides HLA-G and ILT-2, additional IC molecules such as programmed cell death protein-1 (PD-1), cytotoxic T-lymphocyte-associated protein (CTLA-4), T-cell immunoglobulin and mucin-domain containing-3 (TIM-3), and CD95 are associated in tumor-driven immune escape mechanisms acting locally at the tumor site or systemically in the peripheral blood (24)(25)(26). The continuous upregulation and co-expression of multiple IC, being often observed in cancer and chronic infections, are indicative for an immunosuppressive/exhausted phenotype of T cells and are associated with loss of effector functions and immunosurveillance (27,28).…”
Section: Introductionmentioning
confidence: 99%